Deposition of sulfate aerosols with positive Δ33S in the Neoarchean. (15th September 2020) - Paris, Guillaume; Fischer, Woodward W.; Johnson, Jena E.; Webb, Samuel M.; Present, Theodore M.; Sessions, Alex L.; Adkins, Jess F.
Abstract: Anomalous sulfur isotope compositions present in Archean rocks have been intensely scrutinized over the last 20 years because they record key aspects of Earth's atmospheric composition prior to the appearance of free molecular oxygen ca. 2.3 billion years ago. These isotopic compositions can be described as mass anomalous fractionations (MAF) and are produced in the atmosphere as UV light interacts with SO2 molecules. Most interpretations suggest that atmospheric processes generate a reduced S-phase with a positive ( 33 S-enriched) MAF signature, as measured in pyrites, and an oxidized S-phase with a negative anomaly, as measured in bedded barite deposits. However, recent data for carbonate-associated sulfate (CAS) — a direct proxy for the isotopic composition of sulfur from seawater sulfate — in Neoarchean rocks showed no such negative values, but rather the opposite. To understand if the positive MAF anomalies we measured in Neoarchean CAS reflect secondary processes (diagenetic, metamorphic, handling) instead of original signals of Archean seawater sulfate, we collected additional sample suites with various degrees of preservation and metamorphic alteration across the Campbellrand-Malmani platform in South Africa. Results illustrate that within this comprehensive suite, less-altered samples all contain positive MAF values while secondary processes tend to either remove CAS from the sample and/or decrease the 33 S-enrichment. This positive MAF signal in sulfate is therefore reasonably interpreted as a primary depositional origin, and implies that the assumption that sulfate always carries a negative MAF anomaly throughout the Archean rock record needs to be reconsidered. Our CAS observations suggest that future experiments and calculations should also consider atmospheric and/or sulfur cycling processes that can produce oxidized sulfur with a positive MAF signature.